Sweet Potato Leaf Extract Gummy Candy as an Antioxidant-Rich Functional Food for Stunting Prevention in Children - Udayani, Ni Nyoman Wahyu; Gelgel Wirasuta, I Made Agus; Nindya Kartika, Dewa Ayu Kintan; Anggreni, Ayu Putu Puspa (State University of Gorontalo, 2025)
Stunting remains a major public health concern linked to oxidative stress and micronutrient deficiencies. This study aimed to develop and evaluate gummy candy formulations containing sweet potato leaf extract (Ipomoea batatas L.) as a functional food candidate for stunting prevention in children. The extract was obtained by maceration, and the formulation was evaluated through phytochemical screening, sensory evaluation, weight uniformity, antioxidant activity using the DPPH method, and mineral content analysis with atomic absorption spectrophotometry (AAS). Phytochemical analysis confirmed the presence of flavonoids, tannins, and saponins. Sensory evaluation by 30 panelists indicated observable differences between formulations: F0 (control) was preferred in terms of color and taste, while F1 (with extract) presented a darker green-purple appearance and a slightly bitter aftertaste, though texture remained similar in both. Weight uniformity results met pharmacopeial standards, with coefficient of variation values below 5%. Antioxidant activity testing revealed strong radical scavenging potential of the extract (IC₅₀: 29.263 ppm), moderate activity in the F1 gummy (IC₅₀: 108.245 ppm), and very weak activity in F0 (IC₅₀ 200 ppm), compared to ascorbic acid as a positive control (IC₅₀: 6.426 ppm). Mineral analysis of F1 showed iron content of 168.94 ppm and zinc content of 28.05 ppm, contributing significantly to daily nutritional requirements. In conclusion, the incorporation of sweet potato leaf extract into gummy candy provides bioactive compounds with antioxidant activity and essential minerals, while maintaining acceptable sensory quality. These findings support its potential development as a functional food to contribute to stunting prevention strategies in children.